Sympathetic Nervous System and Exercise Affects Cognition in Youth (SNEACY): study protocol for a randomized crossover trial. - Raine, Lauren B.; McDonald, Katherine.; Shigeta, Tatsuya T.; Hsieh, Shu-Shih.; Hunt, Jennifer.; Chiarlitti, Nathan A.; Lim, Michelle.; Gebhardt, Kristen.; Collins, Nina.; Lisio, Michael.; Mullen, Sean P.; Kramer, Arthur F.; Hillman, Charles. (Tufts University. Tisch Library., 2021)
Keywords: Brain function, Executive control, Neuroimaging, Physical activity, Children.; Springer Open.